Generational IQ test score changes and the positive manifold of intelligence: evidence from Austrian Air Force pilots and air traffic controllers (1992–2016) - Oberleiter, Sandra; Wurzer, Jana; Mikas, Michael; Held, Martin; Wieland, Bettina; Zeilinger, Elisabeth L.; Voracek, Martin; Pietschnig, Jakob (Frontiers in Psychology, 2025)
Increasingly inconsistent generational IQ test score change patterns across recent decades have been suggested to be due to increased ability differentiation as a consequence of cross-temporally decreasing strengths of the positive manifold of intelligence. Here, we investigate the Flynn effect and directly test the idea of a changing positive manifold, based on the performance of N = 204 Austrian Air Force pilots and air traffic controllers across twelve IQ subtests. Subscale change scores indicated consistent gains in measures related to the CHC (Cattell-Horn-Carroll) stratum II domains of fluid reasoning, quantitative knowledge, and retrieval. However, change patterns in the stratum II domains working memory and comprehension knowledge were ambiguous and suggest stratum I-based differentiation of the Flynn effect. In all, our results indicate positive and substantial Flynn effects in the majority of examined subscales, but no evidence for any meaningful changes in the positive manifold strength.